Anti‐TNF alpha medications and neuropathy - Tsouni, Pinelopi; Bill, Olivier; Truffert, André; Liaudat, Christelle; Ochsner, François; Steck, Andreas J.; Kuntzer, Thierry (Journal of the peripheral nervous system, 2015)
We studied the clinical, electrophysiological, and pathological features, outcome, and frequency of anti‐tumor necrosis factor alpha (a‐TNF) medications‐induced neuropathies (ATIN) in patients with inflammatory disorders. Of 2,017 patients treated with a‐TNF medication, 12 patients met our inclusion criteria for a prevalence of 0.60% and an incidence of 0.4 cases per 1,000 person‐years. The median time from a‐TNF medication treatment to ATIN was 16.8 months (range 2–60 months). Six patients had focal or multifocal peripheral neuropathies. The other six had generalized neuropathies. For all, a‐TNF medication was stopped. Seven patients received immunoglobulin infusions. ATIN outcome was favorable in all but one patient. ATINs are rare and heterogeneous neuropathies. In 10 patients, the neuropathy was “inflammatory”, suggesting that it could be due to systemic pro‐inflammatory effects of a‐TNF agents.